An Enzymatic N‐Acylation Step Enables the Biocatalytic Synthesis of Unnatural Sialosides. (3rd February 2020) - Laborda, Pedro; Lyu, Yong‐Mei; Parmeggiani, Fabio; Lu, Ai‐Min; Wang, Wen‐Jiao; Huang, Ying‐Ying; Huang, Kun; Guo, Juan; Liu, Li; Flitsch, Sabine L.; Voglmeir, Josef
Abstract: Chitin is one of the most abundant and cheaply available biopolymers in Nature. Chitin has become a valuable starting material for many biotechnological products through manipulation of its N ‐acetyl functionality, which can be cleaved under mild conditions using the enzyme family of de‐N‐acetylases. However, the chemoselective enzymatic re‐acylation of glucosamine derivatives, which can introduce new stable functionalities into chitin derivatives, is much less explored. Herein we describe an acylase (CmCDA from Cyclobacterium marinum ) that catalyzes the N‐acylation of glycosamine with a range of carboxylic acids under physiological reaction conditions. This biocatalyst closes an important gap in allowing the conversion of chitin into complex glycosides, such as C5‐modified sialosides, through the use of highly selective enzyme cascades. Abstract : Reversibel und chemoselektiv : Das Enzym Chitobiose‐Deacetylase aus Cyclobacterium marinum, das hoch selektiv monomeres GlcNAc als Substrat akzeptiert, katalysiert die N‐Acylierung von Glucosamin mit Carbonsäuren unter physiologischen Reaktionsbedingungen. Dieser Biokatalysator wurde für die erste vollständig enzymatische Synthese C5‐modifizierter Sialoside aus Glucosamin und unterschiedlichen nichtaktivierten Carbonsäuren verwendet.